2018
DOI: 10.1186/s12906-018-2088-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pelargonium sidoides and Coptis chinensis root inhibits nuclear factor kappa B-mediated inflammatory response in vitro and in vivo

Abstract: BackgroundPelargonium sidoides (PS) and Coptis chinensis root (CR) have traditionally been used to treat various diseases, including respiratory and gastrointestinal infections, dysmenorrhea, and hepatic disorders. The present study was conducted to evaluate the anti-inflammatory effects of a combination of PS and CR in vitro and in vivo.MethodsThe in vitro effects of PS + CR on the induction of inflammation-related proteins were evaluated in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. The levels of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Recent studies have shown that these herbs have antioxidant, anticancer, and anti-inflammatory pharmacological activities [17,18]. In addition, we previously reported that PS + CR had potent anti-inflammatory activities, in vitro and in vivo [19].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recent studies have shown that these herbs have antioxidant, anticancer, and anti-inflammatory pharmacological activities [17,18]. In addition, we previously reported that PS + CR had potent anti-inflammatory activities, in vitro and in vivo [19].…”
Section: Introductionmentioning
confidence: 94%
“…PS and CR were prepared and supplied by Korea United Pharm. Inc. (Seoul, Korea) [19]. In this study, CMC stock solution was dissolved in distilled water at a concentration of 5 mg/ml and autoclaved at 121°C for 20 min using a general and commercial autoclave (DAC-40, Woori Science, Seoul, Korea).…”
Section: Preparations Of Ps + Crmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the negative value of ZP, the better the stability. Accordingly, highly stable particles have fewer chances of aggregation and this is a crucial requirement for the particles to maintain their properties [14]. This will then qualify them for biomedical applications.…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 99%
“…On the other hand, Pelargonium sidoides (PS) is an important medicinal plant that is native to Southern Africa. Among other parts of PS, the roots have been extensively used in the treatment of ailments such as common cold and cough, dysmenorrhea, gastrointestinal and respiratory disorders, hepatic disorders and diarrhea [14]. These claims were validated by modern research results whereby the roots of PS showed potent antiviral, antifungal, antibacterial [15], antioxidant [16], and antimicrobial [17] properties.…”
Section: Introductionmentioning
confidence: 99%